The Quran Memorization Method at TPQ Al-Kaustar, Hidayatullah Foundation, Kukup Koya Koso Village, Jayapura City, Papua Province - Muhammad Fazis; Zulkipli Nasution; Dhafi Zein Fitri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Muslims have a duty to preserve the Qur'an from ancient times to the present, whether by reading, writing, or even memorizing it. This is done to ensure that the Qur'an's validity is maintained during the time of change and replacement. The Tahfiz Al Qur'an methodology is discussed in this paper at the TPQ Al-Kaustar Hidayatullah Foundation Kampung Kukup Jayapura City Papua Province. This research was conducted using a qualitative technique and by gathering data via observations, interviews, and documentation. The findings of this study lead to the conclusion that the TPQ Al-kaustar Hidayatullah Foundation employs a variety of strategies in tahfidzal al-Qur'an activities, including reading each verse of the Qur'an that will be learned one at a time and always reading and memorizing simultaneously.